PENGARUH SUBSTITUSI KULIT SEMANGKA TERHADAP KUALITAS ES KRIM - Pertiwi, Rahmi; Syarif, Wirnelis; Holinesti, Rahmi (Journal of Home Economics and Tourism, 2017)
The background of this study was the lack of utilization of watermelon peel onvariation of foods because it was considered not beneficial, so it became unuseblewaste, whereas watermelon peel has nutritional content and was a potential source ofpectin that can prevent ice cream quickly melted. The purpose of this research was toanalyzed substitution effect of watermelon peel as much as 10%, 15% and 20% tothe quality of color, aroma, texture and taste of ice cream. This type of research waspurely experimental with a completely randomized design method. The data usedwere primary data sourced from 30 semi-trained panelists by proposed theorganoleptic test format. Analyzed of data using ANAVA, if Fcount> Ftable thencontinued with Duncan test. The result of the research showed that there was asignificant influence of watermelon peel substitution on ice cream quality as much as20% produced the best quality, covering aroma (watermelon peel), texture (smooth),texture (not crystalized) and texture (not easy to melted).Keywords: Watermelon peel, Ice Cream, Quality